AI powered sustainable inventory & policy monitoring 1 - Pesqueira, Antonio (Henry Stewart Talks, 2026)
AI-enabled efficiency, Supply chain sustainability, Digital risk integration, Generative AI integration, Smart forecasting, The human contribution, Multi-agent systems